Building multiscalar sustainable ocean governance: How do global perspectives interact with the Portuguese national approach? - Costa, C. M.; Santos, A. T. (Heliyon, 2024)
UNESCO's Intergovernmental Oceanographic Commission launched the United Nations Decade of Ocean Science for Sustainable Development in 2021 to boost global and sustainable Ocean governance. The initiative resulted from historical and political dynamics at the global and lower political scales, with maritime environmental and economic concerns becoming more prominent in 2010. The Ocean Decade's pillars include science and research, sustainability, conservation, and bridging gaps for a global Ocean-Climate-Biodiversity nexus. The Sustainable Development Goals recognized the importance of oceans and marine resources, and the Ocean was officially perceived as a determining factor of Climate Change at CoP 21 in 2015. Portugal has built integrated and far-reaching policies for ocean governance, including significant involvement with an international perspective since the Lisbon World Exhibition in 1998. In addition, the national government established a Ministry of the Sea in 2015 to re-develop relations with its maritime space. This article analyzes and compares the discourse of the United Nations' Sustainable Development Goals reports and the Portuguese government programs (2005–2022) to explore the prominent trends in Portuguese Ocean governance discourse and how global and national perspectives interact. Through this case study, the research aims to develop insights into the multiscalar impacts of promoting global and sustainable Ocean governance and its interaction with national perspectives.